2007
DOI: 10.1007/s00221-007-1020-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hands posture on mental rotation of hands and feet

Abstract: Behavioural and functional neuroanatomy studies demonstrate that mental rotation of body parts is carried out through a sort of inner motor simulation. Here we examined whether changes of hands posture influence the mental rotation of hands and feet. Twenty healthy subjects were asked to verbally judge the laterality of hands and feet pictures in two different postural conditions. In one condition, subjects kept hands on their knees in anatomical position; in the other, their hands were kept in an unusual post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
134
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(168 citation statements)
references
References 38 publications
19
134
3
1
Order By: Relevance
“…A longer preparation time with a fixed thumb might have increased the influence of the participants' own hand posture, potentially eliciting a stronger posture effect. This assumption, however, is contradicted by the finding that in studies in which a posture effect was observed, no adaptation time was applied previous to the experiment, but the posture was adopted only during the experiment [9,10]. In both experiments, medial-over-lateral-advantage (MOLA) was found regularly for stimuli in palmar view, but not for stimuli in dorsal view.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A longer preparation time with a fixed thumb might have increased the influence of the participants' own hand posture, potentially eliciting a stronger posture effect. This assumption, however, is contradicted by the finding that in studies in which a posture effect was observed, no adaptation time was applied previous to the experiment, but the posture was adopted only during the experiment [9,10]. In both experiments, medial-over-lateral-advantage (MOLA) was found regularly for stimuli in palmar view, but not for stimuli in dorsal view.…”
Section: Discussionmentioning
confidence: 91%
“…He concluded that movements performed mentally would induce motor imagery and would therefore be constrained by anatomical joint characteristics in a similar way as real movements [14]. The use of motor imagery strategies in mental rotation of hands has been corroborated by many authors [e.g., 9,14,23]. Evidence for motor imagery being involved in mental rotation of body parts comes from clinical cases [e.g., 3,4,12,16] and from neuroimaging studies (see [22] for review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endpoint measures (response time and accuracy) were defined as in Ionta et al [25]. Therefore response times <500 or >3500 ms were excluded from analysis, and accuracy reflects correct responses.…”
Section: Data Handlingmentioning
confidence: 99%
“…For example, if people are requested to judge the laterality of hands and feet pictures, while varying the posture of their own hands but not of their feet, then response time varies for hands' judgement but not for feet [25]. Moreover, mental rotation of body parts seems to be influenced by both central and peripheral factors.…”
Section: Introductionmentioning
confidence: 99%